Seagrass diversity profile and water quality in some coastal ecosystems in East Nusa Tenggara, Indonesia - IMELDA TIDORA SOMBO; ENDANG ARISOESILANINGSIH; AIDA SARTIMBUL; NIA KURNIAWAN; CATUR RETNANINGDYAH (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Sombo IT, Arisoesilaningsih E, Sartimbul A, Kurniawan N, Retnaningdyah C. 2025. Seagrass diversity profile and water quality in some coastal ecosystems in East Nusa Tenggara, Indonesia. Biodiversitas 26: 5931-5943. Seagrass ecosystems provide critical services including carbon sequestration, coastal protection, and fisheries support, yet face accelerating degradation from anthropogenic pressures. Indonesia harbors 13 of 60 global seagrass species, with East Nusa Tenggara, Indonesia, supporting exceptional diversity within the Coral Triangle biodiversity hotspot. We analyzed seagrass community structure and water quality relationships across eight coastal locations spanning Timor, Rote, and Alor Islands to establish conservation baselines. Field sampling employed 120 quadrats (1 × 1 m²) along transects at 0.5-2.0 m depths, with species identification following standard taxonomic keys. Seven physicochemical parameters were measured in situ and through laboratory analysis. Eight seagrass species were documented (92% of Indonesia's flora), with coverage ranging from 2,000 to 16,000 individuals/site. Three dominant species, Enhalus acoroides, Thalassia hemprichii, Cymodocea rotundata, occurred at all locations with 39% average coverage. Shannon-Wiener Diversity Index ranged from 1.5 to 2.7 (peak at Onan Ana), with 62.5% of sites maintaining moderate-to-high diversity. Critical environmental stress was widespread: nitrate exceeded standards (0.06 mg/L) at all sites by 100-717% (0.12-0.49 mg/L), temperatures surpassed optimal thresholds (> 33°C) at 50% of locations, and hypoxic conditions (DO < 5 mg/L) occurred at 25% of sites. Principal component analysis explained 69.61% of variation, revealing strong negative correlations between nutrients and diversity (orthophosphate-diversity: r = -0.78; nitrate-richness: r = -0.53). Despite environmental degradation, dominant species demonstrated remarkable resilience. Urgent conservation actions required include: implementing nutrient reduction targeting < 0.06 mg/L nitrate through watershed management, establishing thermal refugia protection at sites maintaining < 30°C, and designating high-diversity locations as genetic reserves for regional restoration programs.